Unravelling the origin of multiple cracking in an additively manufactured Haynes 230. Issue 4 (3rd April 2023) - He, Junyang; Wang, Rui; Li, Na; Xiao, Zhongrun; Gu, Ji; Yu, Hongyao; Bi, Zhongnan; Liu, Weihong; Song, Min
ABSTRACT: In this work, by using multi-scale characterizations from electron channeling contrast imaging (ECCI) to atom probe tomography (APT), we directly evidenced that the massive cracking events in the selective-laser-melted (SLMed) Haynes 230 superalloy are due to the continuous decoration of an M23 C6- type thin film at grain boundaries. The high-melting-point nature of the carbide rules out the possibility of liquidation cracking, while the long and straight film surface facilitates stress-induced solid-state cracking. Impurities, Si, Mn and Fe, greatly enhance the cracking susceptibility despite the interesting fact that they are strongly depleted from the carbide. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The massive cracking events in the selective-laser-melted Haynes 230 superalloy are due to the continuous decoration of an M23 C6 film at grain boundaries, regardless of the detailed cracking modes.